The Influence of the Work Environment on Employee Job Satisfaction at PT. Risa Tour Lombok in Mataram City - I Gusti Ayu Oka N etrawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Employee job satisfaction can be influenced by the work environment in a company. In a positive and conducive environment, it can increase employee motivation, productivity, and loyalty. While a bad work environment can decrease performance and job satisfaction. A good work environment is a major investment for the company. By creating positive things, job satisfaction can be increased. The purpose of the study was to find out that the work environment can have a positive effect on employee job satisfaction. The research method is descriptive analysis with associative quantitative research. The results of the study are at Y = 8.18 + 0.98 X, which means, if a good and positive work environment is optimally improved with a score of X = 90, then Y = 96.38. While the t-test result of 7.44 is greater than the t-table of 2.160, meaning that the work environment has a positive and significant effect on employee job satisfaction at PT, Risa Tour Lombok in Mataram City. Suggestions to company management, to further improve the safe and comfortable working environment, so that workers will be more satisfied, and ultimately also have an impact on employee performance.